Debugging Debugging - Chang, Seokjoo Andrew; Seow, Gim; Tam, Kinsun (Journal of multidisciplinary research (Miami Gardens, Fla.), 2019)
When a computer program fails to accomplish its intended task, software developers typically conduct debugging to identify and remove bugs. This debugging operation itself is not immune to flaws. Empirical evidence suggests many costly bugs appear after shipping of software, which calls into question the effectiveness of the current debugging operation. Failing its mission, the debugging operation itself needs to be debugged. Just like computer professionals, accountants care to safeguard their work against errors. This paper proposes a comprehensive bug control framework modeled on the internal control framework of the accounting discipline, and critically evaluates the status quo of software bug prevention versus bug detection and correction. We conduct Google searches to count matches corresponding to error prevention versus error detection and correction in the contexts of software development and accounting. Relative to accounting, the computer profession tends to emphasize bug detection and correction, which are costly tasks. This article recommends shifting emphasis to bug prevention, and suggests new focuses on programmer training to strengthen bug control.